Mapping the Landscape: A Bibliometric Analysis of Global Trends in Smart Library Research (1992-2023) Using Scopus - Samira Guechairi (International Journal of Information Science and Management)
Using the Scopus database, this study provides a comprehensive bibliometric analysis of global trends in smart library research between 1992 and 2023. One hundred thirty-two documents were retrieved and analyzed through the biblioshiny package in R-Studio and VOSviewer for visualization and mapping. The findings highlight that the Journal of Library Science in China leads the field with 20 articles, and Wuhan University emerges as the most prominent contributor. China is the most productive country with 129 documents and the highest citation count at 389, while Zhang Y is the most prolific author. Co-authorship and citation analysis further illustrate collaborative networks, with a growing interest in the topic in recent years. These insights offer valuable implications for librarians, researchers, and funding agencies by providing a nuanced understanding of key contributors and trends in smart library research. To the best of the author's knowledge, this is the first bibliometric study to map global smart library literature within the Scopus database, offering a foundation for future research and collaboration.